2016
DOI: 10.4314/jasem.v20i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibiotic resistance patterns and heavy metals tolerance of some bacteria isolated from contaminated soils and sediments from Warri, Delta State, Nigeria

Abstract: This work investigated the antibiotic resistance patterns and heavy metals such as Lead (Pb), Zinc (Zn), Cadmium (Cd) and iron (Fe) tolerance of selected bacteria isolated from contaminated soils and sediments around Warri area of Delta State. The heterotrophic bacterial counts for the sampled soils and sediments ranged from 1.7×105 cfu/g to 5.7×105cfu/g for Ubeji river sediments, 1.0×105 cfu/g to 9.0×105cfu/g for spare parts dumpsite and 1.2×104cfu/g to 9.0×104 cfu/g for Ifie depot sites respectively. The cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
(9 reference statements)
1
7
0
Order By: Relevance
“…However, at the tenth week, PCD only enhanced complete removal of Cd on all used lubricating oil contamination levels compared with compost and PCPH only that attained complete removal of Cd on 5% and 15% used lubricating oil contamination levels, respectively (Table 4). In line with the results obtained in this study, Eghomwanre et al (2016)…”
Section: Streptococcus Pyogenes and Enterococcus Faecalis Co-culturesupporting
confidence: 92%
“…However, at the tenth week, PCD only enhanced complete removal of Cd on all used lubricating oil contamination levels compared with compost and PCPH only that attained complete removal of Cd on 5% and 15% used lubricating oil contamination levels, respectively (Table 4). In line with the results obtained in this study, Eghomwanre et al (2016)…”
Section: Streptococcus Pyogenes and Enterococcus Faecalis Co-culturesupporting
confidence: 92%
“…Also, Bacillus and Pseudomonas spp., which can tolerate Cr, Pb, Fe, Hg, and Cu had been documented in previous works (Hassen et al, 1998;Nath et al, 2019;Imron et al, 2021). The mechanisms used by microorganisms to resist/tolerance heavy metals have been linked to modification of their cell membrane regulation, complexation/stabilization, enzymatic transformation/detoxification and plasmid-mediation (Ianeva, 2009;Sevgi et al, 2010;Eghomwanre et al, 2016). The use of extracellular polysaccharides, extracellular and intracellular sequestration by Pseudomonas spp.…”
Section: Resultsmentioning
confidence: 96%
“…which displayed least). The variations in the MICs could be attributed to the differences in their cell wall components and abilities to synthesize proteins with special abilities to bind metals and regulate their effects (Sevgi et al, 2010;Eghomwanre et al 2016;Mosa et al, 2016). A comparison of the four remarkable isolates (Proteus, Providencia, Pseudomonas and Bacillus) revealed that Bacillus spp.…”
Section: Resultsmentioning
confidence: 99%
“…In an earlier study, S. aureus, E. coli and P. aeruginosa were reported as the most resistant isolates to antibiotics and these isolates apart from S. aureus showed MDR in our study. Furthermore, these MDR in their study showed abundant to moderate growth with iron and zinc at higher concentrations [ 39 ]. Compared to our findings, B. cereus, B. subtilis, and E. coli all showed complete resistance to Pb.…”
Section: Discussionmentioning
confidence: 99%
“…Isolates showing multiple drug resistance (resistance to atleast 2 antibiotics) were selected for heavy metal resistance test. This was done using as previously reported [ 26 , 39 ]. Briefly, a loopful of 12–16 h old bacteria culture in tryptic soy broth was inoculated on Mueller- Hinton Agar plates bearing different concentrations (50, 100, 150, 200 and 250 μg/ml) of the test heavy metal (chromium, vanadium, cobalt, cadmium and lead).…”
Section: Methodsmentioning
confidence: 99%